Changes in the craniofacial complex and alveolar bone height of young adults: Applications to dental medicine. Issue 8 (13th September 2016) - Choi, Sung‐Hwan; Jung, Si‐Nae; Cha, Jung‐Yul; Hu, Kyung‐Seok; Kim, Kee‐Deog; Baik, Hyoung‐Seon; Hwang, Chung‐Ju
Abstract : The few studies on craniofacial complex changes in adults have reported contradictory findings. The aim of this study was to radiographically evaluate changes in the craniofacial complex and alveolar bone height of young adults over a 4‐year period. This prospective study included 82 young adults (62 men; mean age, 19.0 ± 0.8 years; 20 women; mean age, 18.8 ± 0.9 years). Three radiographic examinations were performed longitudinally: the first (T0) was conducted at the start of the study, the second (T1) was conducted 2 years later, and the third (T2) was conducted at the end of the study period. As part of these examinations, lateral cephalograms, maxillary and mandibular anterior periapical radiographs, and bilateral posterior bitewing radiographs were obtained. During the 4‐year follow‐up period, all linear cephalometric measurements were significantly greater in men than in women. The amount of increase in the anterior facial height between T1 and T2 was lower in women than in men ( P = 0.029). The rate of uprighting of the upper incisors was lower in men than in women over time ( P = 0.020). The apex of the nose moved inferiorly between T0 and T2 ( P = 0.006). The average overall change in the alveolar bone height was 0.27 mm and the yearly change was 0.07 mm over the 4‐year period ( P < 0.001). Significant changes in the skeletal, dental, and soft tissue, as well as, natural changes in alveolar bone, occur in young adults over time. Clin. Anat. 29:1011–1017, 2016. © 2016 Wiley Periodicals, Inc.